A comparative study of waste activated sludge disintegration by electrochemical pretreatment process combined with hydroxyl and sulfate radical based oxidants. Issue 4 (August 2020) - Sari Erkan, Hanife; Onkal Engin, Guleda
Abstract: In this study, electrochemical treatment (EC) combined with hydrogen peroxide (HP), calcium hypochlorite (CHC), peroxymonosulfate (PMS) and peroxydisulfate (PDS) was investigated as a pretreatment process for improving waste activated sludge (WAS) disintegration in terms of soluble chemical oxygen demand (sCOD). A pair of Fe-Fe electrodes were used in the study, and the main operation parameters were determined as oxidant dosage, initial pH, applied current, electrolysis time and concentration of electrolyte solution (Na2 SO4 ). The maximum disintegration degrees in terms of the COD (DDCOD ) values were found 11.80 %, 11.11 %, 9.61 % and 10.65 % for EC combined with HP, CHC, PMS and PDS treatments at the optimized conditions, respectively. DD values were also calculated for total organic carbon (TOC) and total nitrogen (TN) concentrations after the pretreatment at the optimum conditions, and lower DDTOC values and almost equal DDTN values to DDCOD were obtained. Capillary suction time analyses were performed to determine WAS dewaterability, and reductions of 27.34 %, 29.25 % and 36.13 % CST were found for EC combined with the CHC, PMS and PDS treatments, respectively. EC-HP combination did not enhance WAS filterability, as the CST value increased from 13.1 s of raw sludge to 18.1 s of HP-treated sludge. Extracellular polymeric substance (EPS) types and concentrations were also investigated at the optimized conditions, and the concentrations of polysaccharide and protein increased in soluble EPS (S-EPS). On the other hand, both protein and polysaccharide components decreased in loosely-bound EPS (LB-EPS) and tightly-bound EPS (TB-EPS) in almost all treatments. EC-HP pretreatment was found to be the best combination in order to enhance disintegration of WAS, whereas EC-PDS combination was the best for WAS dewaterability, among all treatment application.